Decreased mixed lineage leukemia 1 is involved in endometriosis-related infertility. (January 2021) - Wen, Xue; Xiong, Yao; Liu, Huimin; Geng, Ting; Jin, Ling; Zhang, Ming; Ma, Ling; Zhang, Yuanzhen
Abstract : The aberrant histone methylation patterns contribute to the pathogenesis of endometriosis (EM). Mixed lineage leukemia 1 (MLL1), a histone methyltransferase, is crucial for gene expression by catalyzing the trimethylation of histone 3 lysine 4 (H3K4me3) in gene promoter. This study aimed to explore whether MLL1 is involved in EM-related infertility. The expressions of MLL1 and H3K4me3 were analyzed in the eutopic endometria from EM women with infertility ( n = 22) and the normal endometria from EM-free women ( n = 22). Mouse EM model was established. The MLL1 and H3K4me3 expression patterns in mice endometria of early pregnancy were also investigated. Immortalized human endometrial stromal cells (iESCs) were cultured and underwent in vitro decidualization. The chromatin immunoprecipitation followed by deep sequencing (ChIP-seq) was performed to find the target gene of MLL1 during decidual process. Results showed that both MLL1 and H3K4me3 decreased in the eutopic endometrium from EM patients compared to that in the normal endometrium. During early pregnancy and the decidual process, MLL1 and H3K4me3 were significantly upregulated in stromal cells. ChIP-seq and ChIP-qPCR found that the cytochrome c oxidase subunit 4I 2 ( COX4I2 ) was directly targeted by MLL1. The dominance of COX4I2-containing enzyme induced the expression of hypoxia-inducible factor-2α (HIF-2α), whose expression in the peri-implantation endometrium is essential for embryo implantation. Further results showed that MLL1 was directly regulated by progesterone (P4) – P4 receptors (PRs). Our study proved that MLL1 was involved in EM-related infertility, which may provide a novel approach to treat the nonreceptive endometrium in EM patients.